2019
DOI: 10.5539/gjhs.v11n7p154
|View full text |Cite
|
Sign up to set email alerts
|

The Perspectives of Amateur Soccer Players and their Coaches on the Use of Performance Enhancing Substances

Abstract: Adolescent and youth sports seem to have progressively developed in South Africa to the point where young athletes are considering doping and the use of performance-enhancing substances (PES). This study determined the perspectives of U-19 soccer players and their coaches in the eThekwini region, KwaZulu-Natal, South Africa, on the use of supplements and drugs. Male participants (n = 449) playing first team soccer from development clubs in the eThekwini region, and their respective coaches (n = 30), volunteere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[ 21 ] A study on amateur soccer players reported that coaches recommended energy drinks to players. [ 8 ] In the current study, participants mainly relied on online sources and coaches for advice in choosing a supplement for use. Athletes frequently use caffeine-containing beverages before a soccer match to enhance performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] A study on amateur soccer players reported that coaches recommended energy drinks to players. [ 8 ] In the current study, participants mainly relied on online sources and coaches for advice in choosing a supplement for use. Athletes frequently use caffeine-containing beverages before a soccer match to enhance performance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Sports and energy beverages are also commonly known about and used by amateur athletes. [ 8 ] This increasing trend in the use of supplements is also evident in African countries. Fifty-one per cent of soccer players in the Zimbabwean league used dietary supplements, mainly vitamins (20%) and minerals (17%); while 15% reportedly consulted traditional healers for herbal supplements.…”
mentioning
confidence: 98%
See 1 more Smart Citation